2021
DOI: 10.3233/jad-201580
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Isolation on People with Dementia and Their Family Caregivers

Abstract: Background: People with dementia and their family caregivers may face a great burden through social isolation due to the COVID-19 pandemic, which can be manifested as various behavioral and clinical symptoms. Objective: To investigate the impacts of social isolation due to the COVID-19 pandemic on individuals with dementia and their family caregivers. Methods: Two semi-structured questionnaires were applied via telephone to family caregivers of people diagnosed with dementia in three cities in Argentina, Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 32 publications
3
70
0
5
Order By: Relevance
“…Similarly, people living with cognitive impairment are particularly subjected to the effects of social isolation that negatively impact their cognitive and affective well-being ( 29 ). The pandemic seems thus to have done nothing but worsen an already existing framework of frailty typical of this population ( 30 , 31 ). Interestingly, in our study this happens in the most cognitively impaired individuals that might be considered as already so compromised that social isolation cannot hit them furtherly.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, people living with cognitive impairment are particularly subjected to the effects of social isolation that negatively impact their cognitive and affective well-being ( 29 ). The pandemic seems thus to have done nothing but worsen an already existing framework of frailty typical of this population ( 30 , 31 ). Interestingly, in our study this happens in the most cognitively impaired individuals that might be considered as already so compromised that social isolation cannot hit them furtherly.…”
Section: Discussionmentioning
confidence: 95%
“…Emerging evidence describes the effects of lockdown during the COVID-19 pandemic on people with dementia living in the community. One study conducted in three South American countries (including in Chile) found a significant decline in memory function (among 53% of people with dementia) as well as increased levels of sadness (31%) and anxiety (37%), with family caregivers feeling more tired and overwhelmed [11]. Therefore, those living with dementia are considered amongst the most vulnerable [3].…”
Section: Inequity In Dementia Care Before and During The Covid-19 Pandemicmentioning
confidence: 99%
“…This, in turn, could substantially increase the incidence for neurodegenerative diseases including dementia [8]. The impact of COVID-19 on dementia and dementia services is likely to be attributable to different causes including the impact of lockdowns and social isolation on the physical and psychosocial health of elderly people or people living with dementia [9][10][11]. Additionally, neurologic manifestations associated with COVID-19 [12] could represent an additional burden for dementia services, although the long-term consequences are unknown, and more studies are needed [13].…”
Section: Introducing a Hypothesis For Translational Learning Of Health Systems In Response To The Covid-19 Pandemicmentioning
confidence: 99%
“…In addition, the pandemic has impacted the management of patients with neurological disorders, with changes in the management of relapses, usual follow-up, diagnostic procedures, implementation or generalization of telemedicine, etc. Lockdown and social isolation were also very harmful in patients with neurological disorders ( 2 ). Furthermore, the treatment of neurological emergencies, such as stroke, was also compromised because of resource re-allocation during the emergency, and the fear of patients to attend the hospital.…”
mentioning
confidence: 99%